(untitled) (Euro-Latin American Journal of Administrative Law, 2025)
Spatial planning has become a key tool for addressing climate change, enabling sustainable land management and the protection of vulnerable ecosystems. In Chile, the introduction of the Regional Spatial Planning Plan in 2018 and the adoption of the Framework Law on Climate Change in 2022 have created an institutional setting in which the climate variable must be incorporated into administrative territorial planning procedures. Spain, with a more established track record, has made progress in integrating climate criteria, although its implementation has led to legal disputes between different levels of government. This study, grounded in the theory of polycentric and multilevel climate governance, identifies the main obstacles to the effective implementation of these instruments through a comparative analysis. The methodology is based on the examination of regulatory frameworks, case law, technical documents, and case studies of two regional spatial planning instruments in Spain. The analysis reveals significant limitations in the Chilean case, such as regulatory incoherence and weak inter-institutional coordination. The Spanish experience, in turn, shows how the politicization of planning and the strategic use of public participation can undermine its effectiveness. Based on these findings, the article identifies key lessons to strengthen climate-oriented territorial governance in Chile.